2019
DOI: 10.21203/rs.2.19400/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PTP1B inhibitor alleviates deleterious microglial activation and neuronal injury after ischemic stroke by modulating ER stress-autophagy axis via PERK signaling in microglia

Abstract: Background : Cerebral ischemia/reperfusion (IR) after ischemic stroke causes microglial activation which lead to neuronal injury. Protein tyrosine phosphatase 1B (PTP1B) emerges to be a positive regulator of neuroinflammation, yet the effect of its inhibition on microglial activation as well as cerebral IR injury is largely unknown. Here we explored whether PTP1B inhibitor sc-222227 attenuates microglial activation and mitigates neuronal injury after cerebral IR injury. Methods : Cerebral IR injury rat model w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…For example, Li [9] et al reported that in ischemic SCI, subcooling reversed the excessive activation of BV2 cells by inducing autophagy. Zhu [10] et al reported that in cerebral ischemia/reperfusion (IR) after ischemic stroke, increased autophagy attenuated IR-induced BV2 activation. This suggests that enhanced BV2 autophagy may be a promising new therapeutic strategy for SCI.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Li [9] et al reported that in ischemic SCI, subcooling reversed the excessive activation of BV2 cells by inducing autophagy. Zhu [10] et al reported that in cerebral ischemia/reperfusion (IR) after ischemic stroke, increased autophagy attenuated IR-induced BV2 activation. This suggests that enhanced BV2 autophagy may be a promising new therapeutic strategy for SCI.…”
Section: Introductionmentioning
confidence: 99%